Inspirasi Kisah Dalam Menstimulasi Character Building Anak Usia Dini - Mariana Mariana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
The greatest trust of parents and educators is to build character and quip a child with knowledge. Television shows are examples of audio-visual media that affect children’s characteristics. Early childhood is a vulnerable age in all directions of learning. Character planting will be formed easily without thinking deeply about themselves. The choice of their chois can make them behave, speak, speak or can be interpreted as the character that grows will resemble what they often hear and see. This research uses qualitative case study approaches. The technique used and data retrieval uses observation, interviews, documentation and data analysis. The object used as the informant in this study was determined purposively, the reasis more, namely eight early childhood on the road Dewi Khunthi Pulosari Jambon Ponorogo. The results of the study show that there are character education values in the cartoon upin and ipin. There is huge enthusiasm of early childhood in the way of Dewi khunthi. That even character figures in animated film Upin and Ipin provide a stimulus in planting the character of early childhood in accordanece with early childhood development, enter and provide effective example in fosting early childhood character.